Manajemen Jalan Napas Sulit pada Pasien Dewasa: Literature Review - Aditya Gloria Monalisa Sianturi; Khadafi Indrawan (CV. Jasa Sukses Abadi, 2026)
Difficult airway is a clinical situation in which a healthcare provider who is skilled at airway management encounters difficulty with one or more standard methods of airway management. Difficult airway may obstruct mask ventilation or increase the risk of failed intubation attempts. The purpose of this literature review is to understand the management of difficult airway on adult patient. The method used in this literature review involved searching for literature published between 2018 into 2023 on NCBI, PubMed, and Google Scholar databases, focusing on management of difficult airway on adult patient. Then, literature was analyzed using systematic literature review method, which included data collection and evaluation activities in accordance with the objective of the literature review. There are several indicators of difficult airway, which are face mask ventilation, laryngoscopy, supraglottic airway ventilation, tracheal intubation and extubation, and invasive airway. In addition, there are several predictors as a reference in identifying difficult airway, which are LEMON mnemonic and MOANS mnemonic. After a difficult airway has been identified, there are several interventions that can be apply, which are awake tracheal intubation, anesthetized tracheal intubation, and mixed intubation.